2022
DOI: 10.1177/00207640221141646
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of loneliness and its correlates among patients with schizophrenia

Abstract: Background: There are limited data on loneliness and its correlates in patients with schizophrenia. Objective: To evaluate prevalence and correlates of loneliness in patients with schizophrenia, currently in clinical remission. Methodology: A total of 160 patients of schizophrenia in clinical remission were assessed on UCLA Loneliness Scale, Positive and Negative syndrome scale, Calgary Depression Scale for Schizophrenia (CDSS), Internalized Stigma of Mental Illness Scale, Rosenberg Self-esteem Scale, Brief CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Our study showed that the loneliness score was high among both of the HPL group. This finding was in line with other studies, which demonstrated that patients with schizophrenia experienced high level of loneliness [1,11]. Our results also showed loneliness had an adverse impact on patients to achieve a high level of HPL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that the loneliness score was high among both of the HPL group. This finding was in line with other studies, which demonstrated that patients with schizophrenia experienced high level of loneliness [1,11]. Our results also showed loneliness had an adverse impact on patients to achieve a high level of HPL.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, patients who have lower education levels and socioeconomic status are prone to have unhealthy lifestyles [ 10 ]. Notably, patients with schizophrenia often experience high level of stigma and discrimination, exacerbating their social isolation [ 11 ] and thereby impeding the development of healthy habits. Several studies have demonstrated that modifiable factors, including poor nutrition, low physical activity level, and high body mass index (BMI) [ 12 , 13 ] are important determinants of CVDs, besides some static factors, such as genetic vulnerability [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies higher level of loneliness was associated higher severity of depression, poorer quality of life and higher use of maladaptive coping in PwS (Suman et al, 2023). Furthermore, PwS loneliness scores predicted a diagnosis of drug abuse (Trémeau et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…SSD are known to severely affect social functioning as they cause deficits in numerous domains relevant to social functioning, such as emotion recognition, emotion processing, and theory of mind [9]. It comes as no surprise that there is a high rate of social isolation in populations with SSD, with a recent study reporting rates of 80% [13].…”
Section: Introductionmentioning
confidence: 99%
“…The social burden of a lack of societal integration does not stay without consequences: for patients suffering from a schizophrenia spectrum disorder (SSD), a positive association between social isolation and depressive and negative symptoms as well as impaired social and cognitive functioning has been shown [14][15][16]. Loneliness has also been found to be associated with increased use of maladaptive coping strategies, higher levels of self-blaming, and lower self-esteem in patients with SSD [13]. In fact, there is also subtle evidence of a reciprocal influence of social isolation and schizophreniform symptomatology: findings from murine animal models strongly support the hypothesis that social isolation leads, in fact, to deficits associated with SSD, such as anxiety and cognitive impairments [17,18].…”
Section: Introductionmentioning
confidence: 99%